Chat with our AI personalities
f(x)= (4 - 5y)/8 f(y)= (4 - 8x)/5
f(x1) = (-5)2 + 3*(-5) + 5.1 = 25 - 15 + 5.1 = 15.1 f(x2) = (6)2 + 3*(6) + 5.1 = 36 + 18 + 5.1 = 59.1 f(x2)-f(x1) = 59.1 - 15.1 = 44 x2 - x1 = 6 - (-5) = 11 So average rate of change = 44/11 = 4
Interpreting the question as "evaluate f(x) = -x2 + 5 for x = 4". This is the same as asking "what is f(4)". To evaluate f(4) just replace each instance of the x in the definition of f(x) by the number 4: f(4) = -42 + 5. The result is -11.
find f'(x) and f '(c)f(x) = (x^3-3x)(2x^2+3x+5
-2